SIGNIFICANCE OF OSTEOPONTIN FOR PREDICTING AGGRESSIVENESS OF PROSTATE CANCER - Lukianova, N.; Zadvornyi Т.; Borikun Т.; Mushii О.; Pavlova А.; Tymoshenko А.; Stakhovskyi Е.; Vitruk, I.; Сhekhun V. (Experimental Oncology, 2023)
Background. Effective prediction of the course of prostate cancer (PCa) and the stratification of treatment tactics largely depend on the use of prognostic markers that reflect the molecular and biological features of tumors. In view of the important role of matricellular proteins in the modulation of the growing tumor and metastasis of the hormone-dependent neoplasms, the aim of the work was to study the expression of osteopontin (OPN) at the protein and mRNA levels in the PCa tissue in order to assess the significance of this protein for predicting the aggressiveness of PCa. Materials and Methods. The work is based on the analysis of the results of the examination and treatment of 83 patients with PCa of stages II—IV. The study of OPN expression at the level of mRNA and protein in the PCa tissue was carried out using methods of the real time polymerase chain reaction and immunohistochemistry, respectively. Results. The OPN expression in the PCa tissue was 1.6 times (p < 0.05) higher in patients with regional lymph node metastases compared to patients without metastases. In patients with a Gleason score of < 7, the OPN expression in the tumor tissue was 1.4 times lower (p < 0.05) than in patients with poorly differentiated PCa. In patients with a high risk of tumor progression, the OPN expression level was 1.4 and 2.1 times higher (p < 0.05) compared to patients with a moderate and low risk of PCa progression. The patients with a high OPN expression level in the PCa tissue had significantly decreased 2-year recurrence-free survival rate (by 25%). Conclusions. The obtained results indicate the expediency of using OPN expression indicators in the tumor tissue to predict the PCa aggressiveness and assess the risk of its recurrence.